2018
DOI: 10.1371/journal.pgen.1007291
|View full text |Cite
|
Sign up to set email alerts
|

Endocytic recycling via the TGN underlies the polarized hyphal mode of life

Abstract: Intracellular traffic in Aspergillus nidulans hyphae must cope with the challenges that the high rates of apical extension (1μm/min) and the long intracellular distances (>100 μm) impose. Understanding the ways in which the hyphal tip cell coordinates traffic to meet these challenges is of basic importance, but is also of considerable applied interest, as fungal invasiveness of animals and plants depends critically upon maintaining these high rates of growth. Rapid apical extension requires localization of cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
80
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 63 publications
(84 citation statements)
references
References 85 publications
(137 reference statements)
3
80
1
Order By: Relevance
“…In the SAR, we continued to observe the presence of membrane sheets, though these were found individually, were in a range of orientations (i.e., not in a parallel organisation) and were connected to many tubular extensions ( Figure 5C3 Our work provides the first indication for an on-site SV delivery mechanism in C. albicans. Indeed, endocytic recycling by way of the trans-Golgi network has recently been shown to be crucial for hyphal tip growth (Hernández- González et al, 2018). From this network, SVs bud either directly into the Spk, or in the SAR from which they are transported the short distance to the Spk, most likely along a network of actin cables that extended into the SAR (Sudbery, 2011).…”
Section: The Secretory Pathway In C Albicans Filamentous Cells Is mentioning
confidence: 99%
“…In the SAR, we continued to observe the presence of membrane sheets, though these were found individually, were in a range of orientations (i.e., not in a parallel organisation) and were connected to many tubular extensions ( Figure 5C3 Our work provides the first indication for an on-site SV delivery mechanism in C. albicans. Indeed, endocytic recycling by way of the trans-Golgi network has recently been shown to be crucial for hyphal tip growth (Hernández- González et al, 2018). From this network, SVs bud either directly into the Spk, or in the SAR from which they are transported the short distance to the Spk, most likely along a network of actin cables that extended into the SAR (Sudbery, 2011).…”
Section: The Secretory Pathway In C Albicans Filamentous Cells Is mentioning
confidence: 99%
“…An important finding of our work is that secretion of inulinase requires functional endosomes, specifically EEs, because ablation of the master RAB of EEs, RabB RAB5 , prevented InuA exocytosis without affecting ER or Golgi glycosylation, whereas ablation of its equivalent in late endosomes/vacuoles, RabS RAB7 , had no effect. In contrast, we have recently reported that ChsB, a chitin synthase that continuously recycles to the PM from the TGN does so by way of a sorting endosome that must be functionally located upstream of EEs, such that ChsB exocytosis is completely independent on RabB RAB5 (Hernández‐González et al, ). Both InuA (this work) and ChsB (Hernández‐González et al, ) require the TGN regulator HypB Sec7 for their exocytosis, but unlike the ChsB pathway, the InuA pathway does not depend on GARP, showing that this tethering complex does not participate in a retrograde step transporting inulinase between the endosomes and the TGN that is necessary for its exocytosis.…”
Section: Discussionmentioning
confidence: 93%
“…A previous study established that after its exocytosis the chitin synthase ChsB recycles from the PM to the TGN by way of a sorting endosome located upstream of EEs. Therefore, ChsB recycling is RabB RAB5 ‐independent, but depends on the GARP complex to arrive at the TGN (Hernández‐González et al, ). Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations